Carrying out embedded implementation research in humanitarian settings: A qualitative study in Cox's Bazar, Bangladesh - Shahabuddin, A. S. M.; Sharkey, Alyssa B.; Jackson, Debra; Rutter, Paul; Hasman, Andreas; Sarker, Malabika (PLOS ONE, 2022)
This article was published in PLOS Medicine by PLOS [ © 2020 Shahabuddin et al. This is an open access article distributed under the terms of the Creative Commons Attribution License] and the definite version is available at: https://doi.org/10.1371/journal.pmed.1003148 The Journal's website is at: https://journals.plos.org/plosmedicine/article?id=10.1371/journal.pmed.1003148